Single and double u-tube ground heat exchangers in multiple-layer substrates - Florides, Georgios A.; Pouloupatis, Panayiotis; Christodoulides, Paul (My University, 2013)
The efficiency of ground-source heat pumps depends on the correct sizing of the associated ground heat exchangers (GHEs). Multiple ground layers with regard to GHE and the presence of more than one loops in each borehole (multiple U-tubes) are sparsely raised in the literature. Therefore the accurate prediction of the performance of the GHE under these conditions is of fundamental importance. A newly developed and validated model is applied to a multiple layer ground regime with different properties and the effect of the layer sequence on the outlet temperature is examined. The model is also modified to allow the study of a double U-tube GHE in a single borehole and the assessment of its efficiency with regard to its building cost. Various configurations are then compared to show that an in-series double GHE is the most efficient. The numerical model developed for energy flows and temperature changes in and around a borehole, when a fluid circulates through single and double U-tubes, is validated upon comparing its results with established experimental results for a single GHE. This model is an improvement of a previous one, based on the time-dependent convection-diffusion equation.
Keywords: Heat pumps; Forecasting; Heat exchangers